A putative twin-arginine translocation system in the phytopathogenic bacterium Xylella fastidiosa - Ciapina, Luciane Prioli [UNESP]; Picchi, Simone Cristina [UNESP]; Lacroix, Jean-Marie; Gertrudes de Macedo Lemos, Eliana [UNESP]; Oedberg-Ferragut, Carmen (Canadian Science Publishing, Nrc Research Press, 2011)
The twin-arginine translocation (Tat) pathway of the xylem-limited phytopathogenic bacterium Xylella fastidiosa strain 9a5c, responsible for citrus variegated chlorosis, was explored. The presence of tatA, tatB, and tatC in the X. fastidiosa genome together with a list of proteins harboring 2 consecutive arginines in their signal peptides suggested the presence of a Tat pathway. The functional Tat dependence of X. fastidiosa OpgD was examined. Native or mutated signal peptides were fused to the beta-lactamase. Expression of fusion with intact signal peptides mediated high resistance to ampicillin in Escherichia coli tat(+) but not in the E. coli tat null mutant. The replacement of the 2 arginines by 2 lysines prevented the export of b-lactamase in E. coli tat(+), demonstrating that X. fastidiosa OpgD carries a signal peptide capable of engaging the E. coli Tat machinery. RT-PCR analysis revealed that the tat genes are transcribed as a single operon. tatA, tatB, and tatC genes were cloned. Complementation assays in E. coli devoid of all Tat or TatC components were unsuccessful, whereas X. fastidiosa Tat components led to a functional Tat translocase in E. coli TatB-deficient strain. Additional experiments implicated that X. fastidiosa TatB component could form a functional heterologous complex with the E. coli TatC component.
Keywords: twin-arginine; Tat transport; Xylella fastidiosa